Work, life and leisure in an urban ecosystem - co-creating Munich as an Entrepreneurial Destination. (September 2020) - Thees, Hannes; Zacher, Daniel; Eckert, Christian
Abstract: Growing urban areas are facing an increased complexity of coordination and sustainable management whereby the handling of the interests of businesses, residents and tourists demands increased flexibility and openness. Such challenges are partly addressed by the concept of an Entrepreneurial Ecosystem. The idea of an Entrepreneurial Destination also adds the perspective of living and leisure and serves therefore as an overarching concept that defines economic roles and activities by highlighting urban attractiveness and the interplay of the abovementioned stakeholders. The conducted case study of Munich aims to explore the interconnectedness of work, life and leisure in an urban ecosystem. To do so, 17 semi-structured interviews are processed using the GABEK® method. Results indicate that residents, entrepreneurs and tourists in Munich benefit greatly from the high attractiveness caused by the interplay and interaction of those groups. Initiatives involving new concepts like coliving, coworking and coexperience have emerged in Munich with the main strength to extended networking and communication of stakeholders. This paper contributes to open the sector- and stakeholder-specific view and to regard urban development as a multidisciplinary approach, which combines entrepreneurship, changing social life concepts, participation and sustainability of regions.